Exploring the Impact of External Workplace Factors on Job Satisfaction and Organizational Commitment Among Higher Education Teachers in Nepal - Kandel, Madan; Joshi, Ramesh Dutta; Aryal, Mahendra (Perspectives on Higher Education, 2025)
This study investigates the role of external workplace factors—work environment, financial benefits, and professional development opportunities—in shaping job satisfaction (JS) and organizational commitment (OC) among teachers at constituent campuses in the Kathmandu Valley, Nepal. The research seeks to understand the interconnectedness of these factors and their implications for improving teacher engagement and institutional outcomes. A mixed-methods approach was employed, incorporating quantitative data from questionnaires and qualitative insights from interviews. A sample of 105 teachers provided responses on their experiences with workplace conditions, financial incentives, and opportunities for growth. Statistical analyses, including correlation, regression, and ANOVA, assessed the relationships among key variables. The study revealed significant positive effects of external factors on both JS and OC. Work environment and professional development opportunities emerged as critical drivers of intrinsic motivation, while financial benefits acted as a key extrinsic motivator. Additionally, job satisfaction mediated the relationship between workplace factors and organizational commitment, demonstrating its central role in fostering teacher loyalty. By addressing external workplace factors and enhancing job satisfaction, institutions can improve organizational commitment among educators. This highlights the need for comprehensive strategies that align institutional policies with teacher aspirations to ensure a motivated and effective teaching workforce. The implication of the study is that educational policymakers and administrators must prioritize supportive work environments, equitable compensation, and ongoing development opportunities to sustain a committed and high-performing teaching staff, ultimately leading to better educational outcomes.